Beneficial Effect of Taraxacum coreanum Nakai via the Activation of LKB1-AMPK Signaling Pathway on Obesity. (18th January 2021) - Shin, Mi-Rae; Kim, Min Ju; Park, Hae-Jin; Han, Jegeun; Roh, Seong-Soo
Abstract : Objective . Liver kinase B (LKB) 1 and AMP-activated protein kinase (AMPK) are master regulators and sensors for energy homeostasis. AMPK is mainly activated via phosphorylation of LKB1 under energy stress. Here, we highlighted the antiobesity effect and underlying mechanism of Taraxacum coreanum Nakai (TCN) in connection with LKB1-AMPK signaling pathway. Methods . Male C57BL/6 mice were fed on a high-fat diet (60% kcal fat; HFD) to induce obesity. Simultaneously, they received 100 or 200 mg/kg TCN orally for 5 weeks. We measured the body weight gain and liver weight along with liver histology. Moreover, the changes of factors related to lipid metabolism and β -oxidation were analyzed in the liver, together with blood parameters. Results . The body weights were decreased in mice of the TCN200 group more than those of the HFD control group. Moreover, TCN supplementation lowered serum triglyceride (TG) and total cholesterol (TC) levels, whereas TCN increased HDL-cholesterol level. Liver pathological damage induced by HFD was alleviated with TCN treatment and accompanied with significant reduction in serum AST and ALT activities. In addition, TCN significantly increased the expression of p-AMPK compared with the HFD control group via the activation of LKB1/AMPK signaling pathway. Lipid synthesis gene like ACC was downregulated and factors related to β -oxidation such as carnitine palmitoyl transferase-1 (CPT-1) and uncoupling protein 2 (UCP-2) were upregulated through peroxisome proliferator-activated receptor (PPAR) α activation. Conclusion . Taken together, these data suggest that TCN treatment regulates lipid metabolism via LKB1-AMPK signaling pathway and promotes β -oxidation by PPAR α ; hence, TCN may have potential remedy in the prevention and treatment of obesity.